Madagascar : Three Years into the Crisis - Auffret, Philippe (World Bank Group, Washington, DC, 2014)
Madagascar is one of the poorest countries in the world and a very high proportion of the population experiences frequent shocks, whether from natural disasters, economic shocks or internal crises of governance. As a consequence, about half the country s population is undernourished. Children between the ages of 6 and 14 face the risks of low human capital development, child labor and marginalization. On the other hand, the Government of Madagascar s commitment to social protection as a national policy was never fully effective. Interventions in social protection have been developed on an ad-hoc basis, often on the initiative of donors. In order to inform the government s policy development, the report proposes a social protection strategy that increases the protection of the population while decreasing its vulnerability, taking into account the existing programs and the differences in exposure to risks between population groups recommendations that emerge from the research.